Gene discovery and genome editing to develop cisgenic crops with improved resistance against pathogen infection. Issue 3 (2nd July 2016) - Kushalappa, Ajjamada C.; Yogendra, Kalenahalli N.; Sarkar, Kobir; Kage, Udaykumar; Karre, Shailesh
Abstract: Resistance in plants against pathogen infection is defined as a spectrum of reduced susceptibility, ranging from moderate susceptibility to a hypersensitive response (complete resistance). The genetic improvement of plants is one option to manage diseases. Several quantitative trait loci (QTLs) for disease resistance have been identified, but these contain many genes and the mechanisms by which resistance is imparted are unknown. These operative factors are crucial to assure precise breeding. Several OMICs tools have emerged, along with genomics, to elucidate resistance mechanisms of plants to pathogens. For example, metabolomics of plant–pathogen interactions have led to the discovery of several complex metabolites that are deposited to reinforce secondary cell walls and prevent the spread of the pathogen beyond the initial infection site. Resistance in plants is largely due to antimicrobial biochemicals and/or the structures formed from them; both these lines of defence may be constitutive or induced following pathogen invasion. Pathogen perception leads to induction of resistance-related (RR) proteins and metabolites. Both constitutive and induced RR metabolites are biosynthesized by metabolic pathway genes. The RR proteins and metabolite biosynthetic genes are regulated by hierarchies of resistance ( R ) genes. A non-functional gene or 'missing link' in this hierarchy can inhibit the regulation of genes in specific metabolic pathway and protein production, thus reducing the amounts of RR metabolites and proteins, as well as the associated resistance. In addition, the non-functional biosynthetic R genes also can limit RR proteins and metabolites. Precise replacement of these non-functional genes ( r ) with functional R genes using genome editing tools, similar to backcross breeding, can significantly improve resistance in commercial crops. The objective of this review paper is to discuss a new concept of resistance, review technologies available for gene discovery, mechanisms of resistance, improvement of the genetic diversity of crop plants based on genome editing tools to produce cisgenic cultivars with durable disease resistance, and the regulatory issues concerning genome editing.